2017
DOI: 10.1016/j.omtn.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Murine Cytomegalovirus Infection in Animals by RNase P-Associated External Guide Sequences

Abstract: External guide sequence (EGS) RNAs are associated with ribonuclease P (RNase P), a tRNA processing enzyme, and represent promising agents for gene-targeting applications as they can direct RNase-P-mediated cleavage of a target mRNA. Using murine cytomegalovirus (MCMV) as a model system, we examined the antiviral effects of an EGS variant, which was engineered using in vitro selection procedures. EGSs were used to target the shared mRNA region of MCMV capsid scaffolding protein (mCSP) and assemblin. In vitro, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The aforementioned EGS forms were tested in cultured human cells and mice for modulating gene expression and blocking viral infection (Bai et al 2010(Bai et al , 2011Li et al 2017;Deng et al 2019).…”
Section: Human Rnase P and Inactivation Of Gene Expression By Egsmentioning
confidence: 99%
“…The aforementioned EGS forms were tested in cultured human cells and mice for modulating gene expression and blocking viral infection (Bai et al 2010(Bai et al , 2011Li et al 2017;Deng et al 2019).…”
Section: Human Rnase P and Inactivation Of Gene Expression By Egsmentioning
confidence: 99%
“…In MCMV-infected mice, the EGS variants were more effective in reducing mCSP expression, decreasing viral production, and increasing animal survival, compared with the natural EGS. The results demonstrated that the EGS variant with higher targeting activity in vitro are also more effective in inhibiting MCMV gene expression in mice [49].…”
Section: Egs-rnasementioning
confidence: 94%
“…Li et al explored the antiviral effects of an engineered EGS variant in targeting the shared mRNA sequence which codes for capsid scaffolding proteins (mCSP) and assemblins of murine CMV (MCMV) in the animals [49]. In vitro, the EGS variant was more active in directing RNase P cleavage of the target mRNA than a natural tRNA by 60-fold.…”
Section: Egs-rnasementioning
confidence: 99%
“…Li and Sheng et al explored the antiviral effects of an EGS variant engineered by in vitro selection procedures using MCMV in an animal model [77]. EGSs were used to target the shared mRNA region of MCMV capsid scaffolding protein (mCSP) and assemblin which is essential for viral progeny production.…”
Section: Egs-rnasementioning
confidence: 99%
“…The results showed that engineered EGS variants with higher targeting activity in vitro are also more effective in inhibiting gene expression in vivo. Furthermore, their findings suggested its possiblility for engineered EGS variants to treat MCMV infections [77].…”
Section: Egs-rnasementioning
confidence: 99%